2018
DOI: 10.3390/genes9030147
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype- and SSR-Based Estimates of Genetic Variation between and within Two Important Elymus Species in Western and Northern China

Abstract: Elymus nutans and Elymus sibiricus are two important perennial forage grasses of the genus Elymus, widely distributed in high altitude regions of Western and Northern China, especially on the Qinghai-Tibetan Plateau. Information on phenotypic and genetic diversity is limited, but necessary for Elymus germplasm collection, conservation, and utilization. In the present study, the phenotypic and genetic differentiation of 73 accessions of the two species were evaluated using 15 phenotypic traits and 40 expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Due to the lack of sufficient genetic information and effective molecular marker systems, the phylogenetic relationship between Opisthopappus (Asteraceae) species remains unclear and unresolved to a certain extent. SSR markers are considered to be one of the most important marker systems for plant genetic studies, with high polymorphisms, high abundance, co-dominance, and genome-wide distribution (Thakur and Randhawa, 2018;Zhang et al, 2018). Compared with the genomic SSRs, EST-SSRs are effective and useful markers for non-model plants, which are easily transferred between related species owing to these regions being more evolutionarily conserved than non-coding sequences (Varshney et al, 2005;Ellis and Burke, 2007;Tahan et al, 2009;Bazzo et al, 2018;Park et al, 2019).…”
Section: Discussion the Development Of Est-ssrs Markers Based On Opismentioning
confidence: 99%
“…Due to the lack of sufficient genetic information and effective molecular marker systems, the phylogenetic relationship between Opisthopappus (Asteraceae) species remains unclear and unresolved to a certain extent. SSR markers are considered to be one of the most important marker systems for plant genetic studies, with high polymorphisms, high abundance, co-dominance, and genome-wide distribution (Thakur and Randhawa, 2018;Zhang et al, 2018). Compared with the genomic SSRs, EST-SSRs are effective and useful markers for non-model plants, which are easily transferred between related species owing to these regions being more evolutionarily conserved than non-coding sequences (Varshney et al, 2005;Ellis and Burke, 2007;Tahan et al, 2009;Bazzo et al, 2018;Park et al, 2019).…”
Section: Discussion the Development Of Est-ssrs Markers Based On Opismentioning
confidence: 99%
“…Seed samples were taken from the center of each plot to avoid border effects. Because of serious seed shattering reported in this species [1], seeds were harvested when the seed moisture content was approximately 45% [44]. Seeds of each plant were air-dried, carefully threshed, cleaned, weighed and stored in paper bags at 20 • C and 15% relative humidity before subjected to seed yield evaluation and other seed measurements.…”
Section: Study Areamentioning
confidence: 99%
“…Siberian Wildrye (Elymus sibiricus L.), which belongs to the genus Elymus (Poaceae: Triticeae), is an important perennial, self-pollinating and cool-season bunchgrass. The grass is native to the high altitude regions of western and northern China [1] and widespread in Asia, Europe and North America [2]. This species has erect naked stems with evenly distributed basal leaves, providing good grazing for livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Although these are wild selfing populations, studies have shown that within-population genetic diversity can be moderate and significant in some of them, and as such they are heterogeneous populations of near-homozygous individual plants. This has been documented in diverse wild populations of grasses, including wild oats in China and the USA [60], Elymus breviaristatus in China [61], Elymus nutans and Elymus sibiricus, important perennial forages, in China [62], Elymus tangutorum, a pasture bunchgrass, in China [63], wild emmer wheat (Triticum turgidum ssp. dicoccoides) in Israel [64], Thinopyrum junceum and Thinopyrum junceiforme in Spain [65], Paspalum dilatatum subsp.…”
Section: Diversity Assurance: Stress-induced Male Sterility Promotes mentioning
confidence: 99%